Cultural diversity and inclusion in UK medical schools. (3rd March 2022) - Forrest, Dominique; George, Sherie; Stewart, Vanessa; Dutta, Nina; McConville, Kevin; Pope, Lindsey; Kumar, Sonia
Abstract: Background: Racially minoritised groups across the globe continue to experience differential outcomes in both health and education. Medical schools can play an instrumental role in addressing both these disparities, by creating inclusive student communities and ensuring that tomorrow's doctors can care for our increasingly diverse populations. Objectives: This collaborative, qualitative study led by three United Kingdom (UK) institutions aimed to explore the perspectives of Heads of Primary Care Teaching (HOTs) on cultural diversity and inclusion across UK medical schools. Methods: In December 2020, five focus groups were conducted remotely with 23 HOTs, or a nominated deputy. We explored participants' opinions regarding opportunities and barriers to cultural diversity and inclusion in medical education, ways to overcome these challenges and shared examples of best practice. Data were transcribed verbatim and thematically analysed by three researchers. Results: Investigators identified six themes from the data: lack of faculty diversity, tokenistic faculty training, institutional mindset, diversifying the formal and hidden curricula, intersectionality and student voice. Conclusion: Medical schools worldwide face similar challenges, uncertainties and opportunities when integrating diversity and inclusion throughout the learning environment. Although the importance of the topic is increasingly acknowledged, current efforts are viewed as being passive and tokenistic, hindered by challenges at multiple levels. Partnership with students and collaboration within and between institutions nationally and internationally will enable us to move forwards with both local and global positive, sustainable change.